Traces of Struggle and the Role of Kiai Ahmad Siradj bin Umar Panularan Surakarta, 1878-1961 - Moh. Mahbub; Moh Ashif Fuadi; Muhammad Nasrudin (UIN Sumatera Utara Medan, 2022)
This research is a biography of Kiai Ahmad Siradj bin Umar Panularan from 1878-1961. The problem discussed in this study is about the struggle for proselytizing and the treasures of the relics of Kiai Ahmad Siradj especially in da’wah. Thie research is qualitative research with a historical approach by collecting past research through books, articles, and online news and amplified by interviews. This research resulted in a conclusion. First, Kiai Ahmad Siradj was a figure who promoted Islamic proselytizing in the 20th century in Surakarta and became a disciple of Kiai Imam Bahri Mangunsari Nganjuk, Kiai Dimyathi Tremas, and Kiai Sholeh Darat. Second, Kiai Ahmad Siradj also joined the Barisan Kiai group, which fought alongside the Hizbullah troops in defending independence, especially in the Solo region. Kiai Ahmad Siradj's struggle in pioneering the Nahdlatul Ulama organization in Surakarta is evidenced by his arrival with Kiai Mawardi at the first NU Muktamar in Surabaya in 1926. Even his descendants became administrators of NU Surakarta, including Kiai Yahya Cholil Tsaquf and Gus Yaqut Cholil Qoumas, Chairman of PBNU and Minister of Religious Affairs, are his descendants. Third, Kiai Ahmad Siradj is known as a saint who has a da’wah bil hikmah (wisdom) is a follower of the Qadiriyyah wa Naqsyabandiyyah who left the pesantren, wirid/dhikr, and the writings of the pesantren book, such as safīnat al-najā, fathu al-qorīb, durratu al-bahiyyah, sullamu al-taufīq which is still stored in the pesantren.